Hubungan Pengetahuan dan Sikap Orang Tua terhadap Tindakan Pencegahan Pneumonia pada Balita di Wilayah Kerja RSUD Meuraxa - Mhd. Hidayattullah; Nurmakiah Nurmakiah (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Pneumonia is one of the leading causes of morbidity and mortality in children, especially in developing countries. Parental knowledge and attitudes play an important role in the prevention of this disease. This study aims to determine the relationship between parental knowledge and attitudes with preventive actions against pneumonia in children under five in the working area of RSUD Meuraxa, Banda Aceh City. A quantitative study with a cross-sectional design was conducted on 59 respondents selected using purposive sampling. Data were collected using a valid and reliable structured questionnaire, and then analyzed univariately and bivariately using the Chi-Square test with a 95% confidence level. Odds Ratio (OR) was used to assess the strength of the relationship. The results showed that the majority of respondents had low knowledge (81.4%) and negative attitudes (79.7%), but most performed good preventive actions (72.9%). There was a significant relationship between knowledge and preventive actions (p = 0.01; OR = 0.031; 95% CI: 0.004–0.244) as well as between attitudes and preventive actions (p = 0.02; OR = 0.073; 95% CI: 0.014–0.389). In conclusion, good knowledge and attitudes were proven to act as protective factors against inadequate preventive actions for pneumonia. Health education interventions need to be strengthened to increase awareness and pneumonia prevention practices in children under five.